Konstruksi Budaya Organisasi Komunikatif Berbasis Komunikasi Interpersonal - Edi Nurhidin (Tribakti: Jurnal Pemikiran Keislaman, 2018)
All of human life dimensions will never free from a conflict. The conflict appears because of difference and occurs into human relationship with each context. In the organization context, conflict happened between organization members often influence their relationship and performance quality until organization goal blocked. Its mean, conflict becomes destruction resource. Therefore, any conflict must be behaved and finished through communication as the organization culture. But, communication implementation done does not direct at mutual understanding achievement and reach consensus which is free from coercion or domination, so that the communication results relationship between organization members broken or even an organization. To resolve the negative impacts, all of organization members need to aware and try to increase their interpersonal communication competency. Beside of that, by replace limited formal communication culture into interpersonal communication to increase their relationships quality. By the method, interpersonal communication becomes more functional and as basic standing at once pacesetter of formation or communicative organization culture development.